Trihinoza - prikaz primera - Saletinger, Rajko (Zdravniški vestnik, 2007)
Background. Trichinosis is a widespread zoonosis acquired by ingestion of undercooked meat infected with the larvae of Trichinella parasites. The disease has variable clinical manifestations ranging from asymptomatic to fatal. Majority of infections is caused by Trichinella spiralis, although there are some cases caused by other species. The dramatic decline of trichinosis reflects changes in industrial practices and increased public awareness. The majority of human cases are now associated with wild game meat and noncommercial pork. The case of previously healthy, young man with trichinosis is presented. The disease was determined with serologic testing and cured with albendazole. The source of infection has not been determined. Conclusions. In patients with fever, mialgias and eosinophilia infection with tissue nematodes should always be taken in consideration. In those who have recently consumed raw or undercooked pork and wild game meat we should think about trichinosis. The disease is rare in Slovenia.
Keywords: diagnosis; Diagnostika; Epidemiologija; epidemiology; Infection; Okužba; okužbe; Preprečevanje in nadzor; prevention and control; Slovenia; Slovenija; therapy; Trichinosis; Trihinoza; Zdravljenje; zoonoze